Stress analysis of defence hole ststem for a uniaxially loaded plate using boundary element method - Tan, Philip Aik Lim (Nanyang Technological University, 2022)
The objective of this project is to investigate the optimal position(s) of a defence hole system in a uniaxially loaded plate using stress analysis through a computational method. The project consists of two phases. The analysis of stress concentration factors (SCF) and stress intensity factors (SIF) due to cracks. Considerations of number, size, location of the defence holes are set out in the analysis of the area of interest. Crack length is varied in the analysis for stress intensity factor. Findings from this computational analysis has good agreement when compared to open literature review.